Phytobia (Diptera: Agromyzidae) from Brazil: new species, new record and a key to the Neotropical species - Viviane Rodrigues de Sousa; Márcia Souto Couri (Zoologia (Curitiba), 2018)
ABSTRACT Phytobia Lioy, 1864 flies occur in all continents. There are four recorded species of these flies in Brazil, but recent expeditions at unexplored areas in the country have revealed that the genus is far more diverse than previously known. Based on material collected in the states of Mato Grosso, Mato Grosso do Sul, and Rondônia (as part of the SISBIOTA Diptera Project), we describe fourteen new species of Phytobia. Additionally, we redescribe P. kallima (Frost), previously recorded only from Panama, and provide a key to the 32 resulting Neotropical species. All descriptions include details and illustrations of the male and female terminalia. The speciemens are deposited in the collections of Museu de Zoologia, Universidade de São Paulo (São Paulo, Brazil) and Museu Nacional, Universidade Federal do Rio de Janeiro (Rio de Janeiro, Brazil).